Serviceability Performance of Fibre Reinforced No Fine Concrete Pavement - Rajasundaravadivel Jeya Prakash; Balu Soundara; Christian Johnson (Zaštita Materijala)
The massive development of the construction industry demands sustainability, and the studies on No Fines Concrete (NFC) will support sustainable development in the field of transportation and highway industry. It is the key requirement of all developing countries like India in order to satisfy three main criteria namely sustainability, serviceability and feasibility in addition to its performance. Application of NFC pavement is itself a sustainable method to manage and discharge the retaining stormwater during heavy floods. Fibre Reinforced No Fine Concrete (FRNFC) was considered, with findings suggesting that the inclusion of fibres has minimal impact on strength characteristics and only marginally reduces the permeability of NFC. However, NFC pavements require regular maintenance to prevent clogging of pores with dust, sediments, and debris, which impairs water flow. A 2 m x 2 m span real-time FRNFC pavement was cast and subsequently subjected to assessment of its serviceability performance. The study examines the performance of FRNFC under clogging and suggests rehabilitation methods to reinstate infiltration capacity. Pressure wash combined with vacuum sweep shows the highest Drainage Efficiency Restoration (DER), maintaining drain ability from 99% to 90% after 12 cycles. Routine pressure wash monthly and vacuum sweep yearly are recommended for proper pavement serviceability and effective stormwater runoff mitigation.